Understanding the Socio-Economic and Educational Status of the Children Working in the Brick Field of Mohanpur Sub-Division of Tripura: An Analytical Study - Nani Gopal Debnath, Dr. Prarthita Biswas, MAM Sameem (Mathematical Statistician and Engineering Applications, 2022)
Education is a lifelong continuous accelerating process through which human organisms are converted to human beings. According to constitution of India the right to education is a fundamental right for all children up to the age of 14. The central government as well as state government are bound to provide free and compulsory education to all the Indian children belongs to the age group of 14 years. Children are like clay, parents and teachers are the architecture who will give the shape to the children for a strong foundation for the nation. We the so called educated people of the society are still overlooking about the burning problem of child labour. We know that no children below 14 years age are permitted to work to any commercial workplace and the person who forced the children to work are also punishable even the parents also. But the scenario is just opposite in each of the brick field in our country as well as in our state. The COVID-19 pandemic situation has increased this burning issue to a pick level. The children of the extremely poor families who used to go to school at least for the attraction towards Mid-Day-Meal now a days they are also moved away from the path of school and started to earn money for their family. This pandemic has also increased the number of child labour in different sectors. This study aims to understand the Socio-economic and Educational status of the children working in the brick field of Mohanpur sub-division of West Tripura district of the state of Tripura. Specially the scenario of the education of the girl child of the brick field worker are really pathetic. These girls are not only lagging behind in the way of education but in respect of health also. The condition of sanitation, hygiene and standard of living is rally pathetic. It is the prime time to lift them from the darken life of illiteracy to the way of light. In this battle lots of constrains and limitations are standing with their rigidity still we must win the battle. We have to provide the light of education to this privileged group by any means.